Perancangan Sistem Pendukung Keputusan Rekomendasi Kualitas Keramik Granite Dengan Metode Fuzzy Tahani - Syifa Dwi Rahmasari (2020)
Each building has a different architecture where the architecture can be seen also from the color, shape and type of ceramics used by the building. Granite ceramics are widely used to beautify buildings such as houses, office buildings, hospitals, civil centers and others. Granite ceramics can also be seen from the needs desired by the user wants to be placed where as architects need granite ceramics to be used on the floor of office space can also be used in bathrooms, meeting rooms. PT. Palapa Ceramics and Granite is an online supplier company that sells various kinds of granite ceramics from various vendors. PT. Palapa Ceramics and Granite uses social media and online sales websites to sell its various kinds of granite ceramics. On the online sales website of PT. Palapa Ceramics and Granite, there has not been a recommendation application for selecting granite ceramics to select the desired granite ceramics with customer criteria that require customers to send messages or call PT. Palapa Ceramics and the Granite. Therefore, the author makes a decision support system using tahani fuzzy methods to speed up and facilitate customers in choosing chilled granite ceramics with chilled criteria. With alternatives provided to provide the best recommendations for customers. The expected results can help PT. Palapa Ceramics and Granite provide the best recommendations to customers.